A Path Analysis of Social Cognitive Theory Implementation in Exclusive Breastfeeding - Rismawati, Normalia Levi; Pamungkasari, Eti Poncorini; Novika, Revi Gama Hatta (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Choosing exclusive breast milk is the best decision made by mothers for the health of mothers and babies, breast milk is the best nutrition for babies in the first 6 months of life. This study aims to identify how Social Cognitive Theory (SCT) factors through self-efficacy, outcome expectation, modeling, and reinforcement in maternal decision-making to determine the choice of exclusive breastfeeding and the success of exclusive breastfeeding. Subjects and Methods: This study uses a cross sectional study approach. The target population is mothers who have children aged 0-6 months in 12 health centers in the Boyolali Regency area. A total of 256 study samples were determined using the Purposive Random Sampling technique. The dependent variable is the selection of exclusive breast milk. The independent variables are self-efficacy, outcome expectation, modeling, reinforcement. Data were collected through questionnaires and multivariate analysis using pathway analysis techniques and using STATA 17. Results: The results of the pathway analysis showed that the selection of exclusive breast milk was directly influenced by self-efficacy (OR= 2.22; CI 95%= 1.22 to 4.02; p=0.009) and strengthening (OR= 5.06; CI 95%= 2.81 to 9.14; p<0.001). The selection of exclusive breast milk was indirectly influenced through self-efficacy by modeling (OR= 1.74; CI 95%= 1.00 to 3.02; p=0.050), outcome expectation (OR= 2.66; CI 95%= 1.55 to 4.56; p<0.001). Influenced by strengthening by outcome expectations (OR= 2.98; CI 95%= 1.70 to 5.23; p<0.001). Conclusion: The choice of exclusive breastfeeding is directly influenced by self-efficacy and strengthening. It is also indirectly influenced by modeling and outcome expectations